White paper on science and technology - the relationship between young people and science and technology : (summary) (The Agency [Tokyo]JP, 1993)
Focuses on the relationship between young people and science and technology. Looks at the trends in declining popularity of science and technology among young people, analyses its background and presents possible measures to be taken in the future. Provides statistics on the current status of science and technology in Japan and other nations.
DC